The Relationship Between Atrial Cardiopathy Biomarkers and Prognosis of Patients With Embolic Stroke of Undetermined Source - Ning, Yuye; Wei, Meng; Song, Wenfeng; Luo, Guogang (Frontiers in Cardiovascular Medicine, 2022)
Objective To compare the proportion of atrial cardiopathy in patients with embolic stroke of undetermined source (ESUS) and other non-cardiac strokes, and to evaluate the prognostic value of atrial cardiopathy biomarkers in patients with ESUS. Methods This retrospective study enrolled patients with ischemic stroke from January 2018 to April 2020 in a single stroke center, and compared the proportion of atrial cardiopathy in (1) ESUS group, (2) large artery atherosclerosis (LAA) group, and (3) small-vessel occlusion (SVO) group. Then, it compared the baseline characteristics between ESUS patients with atrial cardiopathy and cardioembolism (CE) group. In addition, the relationship was compared between the biomarkers of atrial cardiopathy and prognosis in patients with ESUS. Results In total, 316 patients with ischemic stroke were included that included 105 (33.23%) ESUS, 84 (26.58%) LAA, 73 (23.10%) SVO, and 54 (17.09%) CE. Among these patients, patients with ESUS were younger, and had lower triglyceride, lower low-density lipoprotein than non-ESUS group. The proportion of atrial cardiopathy in ESUS group was higher than LAA group or SVO group (42.86 vs. 17.86 vs. 8.22%, p < 0.001). Compared with non-atrial cardiopathy group, patients with atrial cardiopathy were older, had lower EF value, larger left ventricular diameter, and longer PR interval. Among 105 patients with ESUS, 11 (10.78%) cases died, 32 (31.37%) cases had poor functional outcome (mRS >2). In the multivariable model, the risk factor associated with the death risk of patients with ESUS was N-terminal pro-B-type natriuretic peptide (NT-proBNP) >250 pg/ml [p = 0.025, hazard ratio (HR) = 4.626, 95% CI: 1.212–17.652] after a 1-year follow-up. Conclusions Atrial cardiopathy is more common in patients with ESUS, and the characteristics of ESUS patients with atrial cardiopathy are similar to those in patients with CE. NT-proBNP >250 pg/ml is related to the risk of death in patients with ESUS.